Correlations between the structure and superconducting properties of MT-YBaCuO. (June 2020) - Prikhna, T A; Moshchill, V E; Rabier, J; Chaud, X; Joulain, A; Pan, A V; Litskendorf, D; Habisreuther, T.
Abstract: Comprehensive experimental results of fully oxidized (up to YBa2 Cu3 O6, 9-7 ) melt-textured YBaCuO materials with different microstructures are presented. These microstructures are built respectively: (1) with a high dislocations density but almost without twins (after high temperature treatment at 2 GPa) and (2) with a high twin density, but practically free from dislocations and stacking faults (after high temperature oxygenation at 10-16 MPa). It is shown that for attaining high critical current densities and fields of irreversibility ( j c( H ‖ c, 0 T)=9·10 4 A/cm 2, H irr =9.7 T at 77 K), a high twin density in YBa2 Cu3 O6.9-7 matrix of MT-YBCO is required. The density of twins in fully oxidized materials depends on the distances between Y2 BaCuO5 inclusions, larger twin densities are related to shorter distances between inclusions. The influence of phase composition of the initial powder mixtures on the distances between Y2 BaCuO5 inclusions have been characterized and discussed.